Homage to the Black Line : Artists - Students of Marcel Janco pay tribute to their teacher. - Janco Dada Museum, Ein-Hod (Ein Hod : Janco Dada museum, 1989)
Etrog, Sorel ; Beeri, Tuvia ; Bar-Adon, Doron ; Yanive, Claire ; Lahav-Shaaltiel, Ora ; Maestro, David ; Nir Even-Tov, Dina ; Rothenberg, Sidon ; Ronkin, Emmanuel ; Chaaltiel, Joseph
Homage to the Black Line : Artists - Students of Marcel Janco pay tribute to their teacher, Janco Dada Museum, Ein Hod, spring-summer 1989
boek